QUANTITATIVE STUDY OF MORPHOLOGICAL STRUCTURAL VARIATION IN THE Calophyllum brasiliense WOOD - Barreiros, Ricardo Marques [UNESP]; Amaral, Simone Simoes [UNESP]; Oliveira de Matos, Carlos Alberto [UNESP]; Costa, Alex Siqueira [UNESP] (Univ Federal Lavras-ufla, 2016)
Favorable silvicultural and technological characteristics of the species Calophyllum brasiliense Camb. have led to the emergence of commercial plantations. Scientific literature offers only medium and general data on some variables of this species, not reporting specific variables prior to the time of the study, such as age, spacing, among others, perhaps because the wood is mostly from native forests. Given the knowledge gap regarding the characterization of guanandi wood, the aim of this work was to quantitatively study: (i) the morphological structural variation of the wood cells, and (ii) the distinction between juvenile and mature wood, for the species from a pure plantation, whose growth history are known. Five specimens were sampled, within a population of 135 trees, with 13 years of age and 4.0 x 2.5 m spacing. The results indicated average values of 1134, 21.02, 12.88 and 4.07 mu m for the length, width, and diameter of the lumen and mean wall fiber thickness, respectively. 13-years-old guanandi wood was characterized as juvenile.
Keywords: Guanandi; Wood anatomy; Juvenile wood; Fibers; Vessels